KOORDINASI PEMERINTAH DAERAH KABUPATEN KEPULAUAN MERANTI DALAM PENANGGULANGAN BANJIR ROB DI DESA ALAHAIR KECAMATAN TEBING TINGGI TAHUN 2011-2015 - Nurbaity, Iin; Tinov, M.Y Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of conducting this research was to know Kabupaten Kepulauan Meranti local government coordination of tidal flood prevention in Desa Alahair, Kecamatan Tebing Tinggi in 2011-2015. The main problem found in this research was less of communication that occured in the handling of tidal flood prevention in Desa Alahair meanwhile the area affected by tidal flood was getting worse due to the abrasion. The theory used in this research was government management, government coordination and disaster management. This research used analytical descriptive method with qualitative research type. The type of data used in this research was primary data and secondary data generated through the results of direct interviews with informants who knew and understood the problems in the field, documentation and observation.Based on the explanation above, it can be concluded that the relationship affected the implementation of tidal flood prevention were several interrelated functions namely planning and coordination, organizing and coordinating, directing and coordinating which included human behavior, human relations, communication, and leadership. Position and coordination, control and coordination.In addition, there were factors hampered tidal flood prevention in Desa Alahair such were unrealized planning, unharmonious communication, and lack of budget of local government of Kabupaten Kepulauan Meranti.Keywords: Coordination, Prevention, Flood.